High-temperature impedance spectroscopy as a technique for monitoring the initial stages of phase transformations in minerals (exemplified by almandine from the Verkholovskaya garnet mine, Middle Urals) - Zhelunitsyn, I. A.; Mikhaylovskaya, Z. A.; Votyakov, S. L. (Litosfera (Ekaterinburg. Online), 2025)
Research subject and Methods.  The electrical characteristics of an almandine sample from the Verkholovskaya garnet mine (Middle Urals, Russia) were studied using high-temperature impedance spectroscopy in both heating and cooling modes, over a temperature range of 200–900 °С and a frequency range of 1–106 Hz. For this method, electrodes made of platinum and lanthanum-strontium cobaltite were employed. The results were interpreted in combination with thermogravimetric data, X-ray diffraction XRD analyses and diffuse light scattering measurements for almandine powders in their initial state, after annealing at 750 °С and for model synthetic iron oxide Fe 2 O 3 . Results.  In the cooling mode, a linear dependence was observed with a break in the temperature range of 600–625 °С with characteristic activation energies E a   ⬚ 0.58 and 0.81 eV in the low-temperature (200–625 °С) and high-temperature (625–900 °С) regions, respectively. During the heating-cooling cycle an anomaly was noted at 750 °С, where the sample’s resistance remained constant or changed insignificantly with increasing temperature. Analysis of impedance spectroscopy data revealed the onset of decomposition of the almandine sample already at 750 °С. Previously, no changes in phase composition had been reported at this temperature. The initial stage of almandine destruction is accompanied by the formation of nanosized particles of iron oxide Fe 2 O 3  on its surface, which was confirmed by diffuse light scattering data. Traditional methods of detecting changes in phase composition (TG-DTA and X-ray phase analysis) indicate the appearance of the Fe 2 O 3  phase only at temperatures above 750 °С. This may be associated with their insufficient sensitivity and/or the specific morphology of the released Fe 2 O 3  phase. Conclusions.  The impact of minor changes in the phase composition of compounds (initial stages of phase transformations) highlights the potential of impedance spectroscopy as a valuable tool for recording and investigating the early stages of thermal decomposition of both minerals and synthetic materials.